'Beyond the State': The limits of international regulation and the example of abandoned seafarers. (June 2022) - Sampson, Helen
Abstract: This paper contributes to debates about the effectiveness of international regulation and the place of 'the state' in developing and enforcing effective international shipping regulation. It focuses on the example of the Maritime Labour Convention (2006) to highlight some of the challenges and successes of international regulation in defending the rights of workers to 'decent work'. The empirical basis of the paper is a novel analysis of abandonment data which allows for the consideration of the resolution of abandonment cases pre-and-post-MLC. This is the first time that such objective analysis has been used to evaluate the efficacy of MLC. The paper describes the regulatory framework which offers protections to seafarers in such circumstances and the ways in which internationally agreed regulations at the ILO are enforced. It describes the data and analyses the effectiveness of the MLC, in increasing the speed with which abandoned seafarers are repatriated. It discusses the implications of the findings and draws conclusions, relating these to broader discussions of the limits and importance of international regulation. Highlights: Presents new analysis of data on vessel abandonment. Advances debates on effectiveness of MLC. Indicates MLC strengths and weaknesses.